Positive Caricature Transcriptomic Effects Associated with Broad Genomic Aberrations in Colorectal Cancer. Issue 1 (December 2018) - Condorelli, Daniele; Spampinato, Giorgia; Valenti, Giovanna; Musso, Nicolò; Castorina, Sergio; Barresi, Vincenza
Abstract We re-examined the correlation between Broad Genomic Aberrations (BGAs) and transcriptomic profiles in Colorectal Cancer (CRC). Two types of BGAs have been examined: Broad Copy-Number Abnormal regions (BCNAs), distinguished in gain- and loss-type, and Copy-Neutral Loss of Heterozygosities (CNLOHs). Transcripts are classified as "OverT" or "UnderT" if overexpressed or underexpressed comparing CRCs bearing a specific BGA to CRCs not bearing it and as "UpT" or "DownT" if upregulated or downregulated in cancer compared to normal tissue. BGA-associated effects were evaluated by changes in the "Chromosomal Distribution Index" (CDI) of different transcript classes. Data show that UpT are more sensitive than DownT to BCNA-associated gene dosage effects. "Over-UpT" genes are upregulated in cancer and further overexpressed by gene dosage, defining the so called "positive caricature transcriptomic effect ". When Over-UpT genes are ranked according to overexpression, top positions are occupied by genes implicated at the functional and therapeutic level in CRC. We show that cancer-upregulated transcripts are sensitive markers of BCNA-induced effects and suggest that analysis of positive caricature transcriptomic effects can provide clues toward the identification of BCNA-associated cancer driver genes.